DEAD Box Protein 5 Inhibits Liver Tumorigenesis by Stimulating Autophagy via Interaction with p62/SQSTM1. Issue 3 (8th February 2019) - Zhang, Hao; Zhang, Yanqiu; Zhu, Xiaoyun; Chen, Chen; Zhang, Chao; Xia, Yuanzheng; Zhao, Yucheng; Andrisani, Ourania; Kong, Lingyi
Abstract : In hepatocellular carcinoma (HCC), dysregulated expression of DDX5 (DEAD box protein 5) and impaired autophagy have been reported separately. However, the relationship between them has not been explored. Here we present evidence to show that, by interacting with autophagic receptor p62, DDX5 promotes autophagy and suppresses tumorigenesis. DDX5 inversely correlated with p62/sequestosome 1 (SQSTM1) expression in hepatitis B virus (HBV)‐associated and non‐HBV‐associated HCCs. Patients with low DDX5 expression showed poor prognosis after tumor resection. We found that DDX5 overexpression induced, while DDX5 knockdown attenuated, autophagic flux in HepG2 and Huh7 cells. DDX5 promoted p62 degradation and markedly reduced the half‐life of p62. Moreover, DDX5 overexpression dramatically reduced, while DDX5 knockdown promoted, cancer cell growth and tumorigenesis in vitro and in vivo . We found that DDX5 bound to p62 and interfered with p62/TRAF6 (tumor necrosis factor receptor–associated factor 6) interaction. Further findings revealed that the N‐terminal domain of DDX5, involved in the interaction with p62, was sufficient to induce autophagy independent of its RNA binding and helicase activity. DDX5 overexpression decreased p62/TRAF6‐mediated lysine 63‐linked ubiquitination of mammalian target of rapamycin (mTOR) and subsequently inhibited the mTOR signaling pathway. Knockdown of TRAF6 blocked DDX5‐induced autophagy. Furthermore, we showed that miR‐17‐5p downregulated DDX5 and impaired autophagy. Inhibition of miR‐17‐5p promoted autophagic flux and suppressed tumor growth in HCC xenograft models. Conclusion: Our findings define a noncanonical pathway that links miR‐17‐5p, DDX5, p62/TRAF6, autophagy, and HCC. These findings open an avenue for the treatment of HCC.